PEMETAAN PENDERITA HIPERTENSI PADA LANSIA (Studi Pada Wilayah Kerja Puskesmas Sangkub Kabupaten Bolaang Mongondow Utara) - Fachry Rumaf; Christien Gloria Tutu; Bambang Herianto Talamati; Ridwan Putabuga; Chandra Wisnu Nugroho (Fakultas Hukum Universitas Malikussaleh, 2023)
Hypertension is the sixth ranked non-communicable disease in Indonesia. The prevalence of hypertension throughout Indonesia is 34.1 percent. Cases of hypertension in the working area of the Sangkub Health Center in North Bolaang Mongondow Regency in 2020 there were 636 hypertension patients, in 2021 there were 681 hypertension patients, and in 2022 there were 483 hypertension patients. This study uses a type of quantitative research using descriptive research methods with a cross sectional approach. The population in this study were all elderly patients suffering from hypertension in the working area of the Sangkub Health Center, North Bolaang Mongondow Regency, namely 483 people. Determining the sample size in this study used the Krejcie-Morgan table, namely 176 hypertensive patients. Based on the results of the study it can be concluded that the factors of age, gender, heredity, obesity, stress, alcohol consumption habits, and excessive sodium consumption habits are factors that can cause a high risk of hypertension in the elderly in the work area of the Sangkub Public Health Center, North Bolaang Mongondow Regency.